Rationale and design of the STOP-IMH randomised trial: Safety of ticagrelor monotherapy after primary percutaneous coronary intervention for ST-elevation myocardial infarction and the effect on intramyocardial haemorrhage - E.C.I. Woelders; B. Yosofi; D.A.M. Peeters; L.S.F. Konijnenberg; C. von Birgelen; J.B. van Rees; S.C.H. van den Oord; A.A.C.M. Heestermans; B.E.P.M. Claessen; N. van Royen; R.J.M. van Geuns; R. Nijveldt; et al. (International Journal of Cardiology: Heart & Vasculature, 2025)
Background: Ticagrelor monotherapy after 1–3 months of dual antiplatelet therapy (DAPT) has shown to be effective and safe after percutaneous coronary intervention (PCI), including in patients with an ST elevation myocardial infarction (STEMI). Direct omission of aspirin could further reduce bleeding complications and may reduce the incidence and expansion of intramyocardial haemorrhage (IMH), a frequent complication after revascularisation for a STEMI. Methods: This multicentre open label pilot study randomises 200 STEMI patients within 24 hours after primary PCI and before the first subsequent dose of aspirin to ticagrelor monotherapy or ticagrelor plus aspirin for twelve months. As IMH is more frequently observed after an anterior STEMI, IMH and infarct size will be determined with cardiac magnetic resonance (CMR) imaging in 60 anterior STEMI patients. In this subgroup, blood samples will be analysed for biochemical outcomes. Results: The primary safety endpoint consists of major adverse cardiac and cerebral events, and the primary efficacy endpoint is infarct size on CMR. Secondary efficacy endpoints consist of the incidence and extent of IMH determined by CMR, and of clinical bleeding events. Other endpoints include all-cause mortality and biochemical outcomes. Conclusion: The STOP-IMH pilot study compares ticagrelor monotherapy with ticagrelor plus aspirin directly after primary PCI in 200 STEMI patients. We aim to provide a signal of safety regarding ischemic events for the direct omission of aspirin after primary PCI, and to compare the infarct size by CMR between the two treatment strategies in the first week after primary PCI.